Defining the Damaged DNA Mobility Paradox as Revealed by the Study of Telomeres, DSBs, Microtubules and Motors - Mekhail, Karim (Frontiers in Genetics, 2018)
Eukaryotic genomes are non-randomly arranged inside the nucleus. Despite this ordered spatial genome organization, damaged DNA exhibits increased random mobility within nuclear space. This increased random movement is thought to promote DNA repair by facilitating homology search, allowing targeting to repair-conducive nuclear domains, or releasing damage from repair-repressive locations. Recent studies focusing on the relationship between telomeres, DNA repair processes, and nuclear organization have revealed that the disruption of motor proteins or microtubules, which typically mediate the directed motion of cargo, disrupts the random mobility of damaged DNA. These findings define a new biological paradox. Here, I define this as the damaged DNA mobility paradox, describe how it uncovers key gaps in knowledge, and highlight key questions to help guide us towards paradox resolution.